2008
DOI: 10.1103/physreve.77.030102
|View full text |Cite
|
Sign up to set email alerts
|

Absorbing-state phase transitions: Exact solutions of small systems

Abstract: I derive precise results for absorbing-state phase transitions using exact (numerically determined) quasistationary probability distributions for small systems. Analysis of the contact process on rings of 23 or fewer sites yields critical properties (control parameter, order-parameter ratios, and critical exponents z and β/ν ⊥ ) with an accuracy of better than 0.1%; for the exponent ν ⊥ the accuracy is about 0.5%. Good results are also obtained for the pair contact process.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 33 publications
2
10
0
Order By: Relevance
“…Although we have shown analytically that an effective temperature and chemical potential cannot be defined in a consistent manner for the KLS model under Metropolis exchange rates, it is interesting to study numerical examples, to assess the degree of inconsistency. We obtain the stationary solution to the master equation for the KLS model, including exchange with a reservoir at temperature T e and chemical potential µ, on a lattice of 4 × 4 sites, using the method of [27]. In the equilibrium case we verify that ∆E = 0 for T e = T n , independent of the exchange rate p r , as expected.…”
Section: A Numerical Examplessupporting
confidence: 55%
“…Although we have shown analytically that an effective temperature and chemical potential cannot be defined in a consistent manner for the KLS model under Metropolis exchange rates, it is interesting to study numerical examples, to assess the degree of inconsistency. We obtain the stationary solution to the master equation for the KLS model, including exchange with a reservoir at temperature T e and chemical potential µ, on a lattice of 4 × 4 sites, using the method of [27]. In the equilibrium case we verify that ∆E = 0 for T e = T n , independent of the exchange rate p r , as expected.…”
Section: A Numerical Examplessupporting
confidence: 55%
“…While somewhat better than the preliminary study of a model in the CDP class, QSA predictions for the SRW model are not of the quality obtained for the contact process [13]. This appears to be connected with the stronger finitesize effects and corrections to scaling observed for models in the CDP class.…”
Section: Discussionmentioning
confidence: 61%
“…In the contact process [13], quantities such as λ S,L andβ(L) vary quite systematically with system size, leading to precise estimates for critical values via BST extrapolation.…”
Section: B Critical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the studies reported here we sample the quasistationary (QS) distribution of the process, (that is, conditioned on survival), which has proven a very useful tool in the study of processes with an absorbing state [1,30,31]. For this purpose, we employ a simulation method that yields quasistationary (QS) properties directly, the QS simulation method [32].…”
Section: Model and Methodsmentioning
confidence: 99%